Modeling the influence of an electric thruster’s ion beam on its global EMC - Rover, Yannik; Thueringer, Rainer; Probst, Uwe; Volkmar, Chris (Frontiers in Space Technologies, 2023)
This research deals with electromagnetic compatibility (EMC) in the field of electric propulsion (EP). To complete previous investigations, the emissions of a fully operating radio-frequency thruster (RIT)—including its extracted ion beam—were numerically analyzed. The ion beam was simulated and investigated with various characteristics. The simulations were performed by means of transient co-simulation. It is clear that the ion beam had a significant impact on the thruster emissions. Properties such as divergence angle and the conductivity of the beam, which can be directly attributed to the operating point of the plasma discharge inside the thruster, play a major role. The next steps will be to bring together all the knowledge gained about the emissions of the individual thruster components as well as the peripheral electronics.